School Environment Management as The Learning Resources to Develop Student’s Motivation in Learning - Wijayaningsih, Lanny (Universitas Negeri Semarang, 2016)
School environment is the most important thing for growing and developing children in their learning, so they can get the knowledge easily by observing and exploring in their school environment. However not all school have manage and prepare their environment well as a learning resources for children to learn. This literature review aim is to manage the school environment as the learning sources for children of 5-6 years to develop their all potential. The method of this research is descriptive with qualitative approach. The data analysis result showed that objective condition of outdoor environment as the learning resources had well prepared by the teacher before it is used for teaching learning activities. By managing the environment including: planning, implementation and evaluation, children showed their enthusiastic with their environment, so they could be more active in their learning, they also got meaningful learning through their interaction with their environment. The result indicated that using the school environment giving the effectiveness in teaching learning to develop the student’s motivation in learning